Ujaran Satir atau Penghinaan? Analisis Linguistik Forensik terhadap Frasa “Prabodoh Subiantotol” dalam Diskursus Politik Indonesia - J. Anhar Rabi Hamsah Tis’ah; Andri Purwanto; Yakobus M. Langkelang Niron (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the linguistic construction, semantic meaning, pragmatic function, and forensic implications of the phrase “Prabodoh Subiantotol” in Indonesian political discourse. The issue is important because digital political speech often blurs the boundary between democratic criticism, political satire, and insult. This study uses a descriptive qualitative method with a forensic linguistics perspective. Data were collected from audiovisual documentation, online news reports, and public digital responses that discussed the phrase. The analysis focuses on lexical modification, evaluative meaning, speech act function, implied meaning, communicative context, and possible social-legal interpretation. The findings show that the phrase is formed through name modification and wordplay by inserting negative lexical elements into a personal name. Semantically, the elements “bodoh” and “tolol” create a derogatory evaluation. Pragmatically, the utterance functions as political criticism, yet it also targets personal identity. The study concludes that the phrase occupies a grey area between political satire and insult. The study contributes a contextual model for assessing controversial digital utterances